Concurrent removal of benzene, toluene, and P-nitrophenol from water using dielectric barrier discharge plasma - Vaishnavi Gaude Agadyekar; Eshita Kakodkar; Delicia A. Barretto; Ruggero Barni; Claudia Riccardi; Nitesh Joshi (Cleaner Engineering and Technology)
Water bodies are contaminated with organic and inorganic waste, making them unsuitable for consumption. This study, for the first time, carries out the degradation of a single pollutant, p-nitrophenol (PNP), as well as a mixture of pollutants (benzene, toluene, and PNP) in a single go using a dielectric barrier discharge (DBD) plasma reactor. The effects of plasma power and treatment time on pollutant degradation were systematically analysed. For PNP, only 70 ± 5 % degradation was achieved at optimal conditions (18 W power, 2 min) with an energy efficiency of 1.57 mg/kWh at 10 ppm of initial concentration. The increased power levels diminish performance due to quenching effects caused by microfilament interactions with the reactor walls. Hydroxyl radical, superoxide radical, hydrogen peroxide, ozone, nitrate, and nitrite species were quantified to understand degradation mechanisms. The degradation of a mixture of pollutants is also demonstrated in a single go with 55 % and 0.73 gCOD/kWh COD degradation and energy yield. The practicality of plasma-treated water was tested by biochemical oxygen demand (BOD), seed germination, and microbial decontamination study (using Escherichia coli). It is demonstrated that compared to polluted water, plasma-treated water exhibited reduced BOD levels, which reduces its harmful effects on daily usage. The reduced toxicity of water also enhanced germination compared to polluted water. The plasma treatment also impedes the growth of Escherichia coli, even causing its complete inhibition. These results highlight the potential of DBD plasma technology as a promising tool for sewage/contaminated water samples.